Perancangan Kunci Kontak Sepeda Motor Menggunakan E-SIM dengan Jaringan RFID - Laurensius Phillipus Ramawijaya; Dian Widiyanto Chandra (KITA Institute, 2023)
Nowadays, the motorcycle key is assumed to be too old-fashioned because it still uses physical metal, is easily eroded, and is loose. A driver's license (SIM) is a card that needs to be brought when driving. It used the driver as evidence that they have a driving permit from the police. On the other hand, identity cards such as SIMs already have RFID technology. However, this technology is rarely used correctly. This study aims to design a motorcycle security system using RFID and, likewise SIM card model as a motorcycle ignition key. The study showed that the system could perform or operate well. Motorcycle key using RFID as a dummy SIM makes people easier who are careless in putting their motorcycle keys.